The German research consortium for the study of bipolar disorder (BipoLife): a quality assurance protocol for MR neuroimaging data - Vogelbacher, Christoph; Sommer, Jens; Bopp, Miriam H. A.; Falkenberg, Irina; Ritter, Philipp S.; Bermpohl, Felix; Attar, Catherine Hindi; Einenkel, Karolin E.; Gruber, Oliver; Juckel, Georg; Flasbeck, Vera; Hautzinger, Martin; et al. (International Journal of Bipolar Disorders, 2024)
The German multicenter research consortium BipoLife aims to investigate the mechanisms underlying bipolar disorders. It focuses in particular on people at high risk of developing the disorder and young patients in the early stages of the disease. Functional and structural magnetic resonance imaging (MRI) data was collected in all participating centers. The collection of neuroimaging data in a longitudinal, multicenter study requires the implementation of a comprehensive quality assurance (QA) protocol. Here, we outline this protocol and illustrate its application within the BipoLife consortium.
Gesehen am 24.06.2025